2013
DOI: 10.1111/jfb.12060
|View full text |Cite
|
Sign up to set email alerts
|

Haematological response of curimbas Prochiloduslineatus, naturally infected with Neoechinorhynchuscuremai

Abstract: This study evaluated the haematological response of curimbas Prochilodus lineatus, naturally infected with Neoechinorhynchus curemai (Acanthocephala: Neoechinorhynchidae). Thirty-seven fish were captured in October 2010 from the Mogi Guaçu River, Porto Ferreira, SP, Brazil. Infected fish presented increased mean corpuscular volume of erythrocytes, and lower thrombocyte and higher monocyte counts than uninfected fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
5
17
0
2
Order By: Relevance
“…Juveniles and adults of cachama under moderate to severe infection by N. buttnerae have shown hyperaemia, hardening and thickening of the intestinal tissue, and yellowish mucosal secretion of a bluetongue aspect. Such alterations were observed in lower intensity in cachama juveniles, which was associated with low parasitic burden, similarly to that previously reported (Belo et al, 2013). These authors found a positive correlation between the size of fish and number of acanthocephalans and consequently pathological alterations in curimbatá (Prochilodus lineatus Valenciennes) naturally infected by N. curemai Noronha, 1973.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Juveniles and adults of cachama under moderate to severe infection by N. buttnerae have shown hyperaemia, hardening and thickening of the intestinal tissue, and yellowish mucosal secretion of a bluetongue aspect. Such alterations were observed in lower intensity in cachama juveniles, which was associated with low parasitic burden, similarly to that previously reported (Belo et al, 2013). These authors found a positive correlation between the size of fish and number of acanthocephalans and consequently pathological alterations in curimbatá (Prochilodus lineatus Valenciennes) naturally infected by N. curemai Noronha, 1973.…”
Section: Discussionsupporting
confidence: 86%
“…A significant increase in the number of monocytes and a decrease in the number of thrombocytes in curimbatá (P. lineatus) infected by N. curemai (Belo et al, 2013) and pacu (Piaractus mesopotamicus) with chronic inflammatory reaction (Belo et al, 2014) justify the present findings, which showed intense inflammatory reaction composed mainly of macrophages. In fact, the chronic aspect of intestinal lesions in cachama with participation of macrophages and polycarion formation on the inflamed site is the result of the recruitment of monocytes from circulating blood.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Blood extensions were prepared for differential leukocyte count, stained with May-Grünwald-Giemsa-Wright. 200 cells were counted by extension to determine the percentage of each cell type [14].…”
Section: Hematologymentioning
confidence: 99%
“…Also, it is know that fish blood parameters can be influenced by several factors, such as seasonal variations, genetics, age, gender, stock density, stress and water quality (Ekanem et al 2012, Belo et al 2013, Castro et al 2014a, what could explain the lack of information on the reference values of health and ill fish.…”
Section: Introductionmentioning
confidence: 99%